CORRELATIONS BETWEEN THE LONG-SPAN FIXED DENTAL PROTHESES AND PERIODONTAL TISSUES MODIFICATIONS - Alice Arina Ciocan-Pendefunda; Alina Mihaela Apostu; Magda-Ecaterina Antohe; Cristina Gena Dascălu; Oana Țănculescu (Romanian Society of Oral Rehabilitation, 2021)
The aim of the study is to determine by finite element analysis the existence of direct correlations between the abutment periodontal tissues condition and the cantilever bridge in the context of functional occlusion. A 3D reconstruction of the mandible, premolars, canines, incisors and of the dental bridge was created, using AutoCAD 2019 and ALGOR 15 FEMPRO software for mesh-area of the structures. The maximum stress was recorded in the periodontal ligament of the first premolar since this load configuration produces a first-degree lever effect with a fulcrum located on the 35 root apex. When the support is on 35, the stress is lower in the bridge area, mainly due to the elimination of the tilting effect, unlike the support at level 34, when the stress distribution is lower than in the first case and the stress on the bridge is higher in the support area, with compression of 34 ligament towards the canine and an elongation from 35. The overstress of periodontal ligament under occlusal forces leads implicitly to the tearing of the ligament fibers either in their body, or in its insertion into the dentin and bone.